Spotlighting graphene quantum dots and beyond: Synthesis, properties and sensing applications. (December 2017) - Ozhukil Valappil, Manila; K. Pillai, Vijayamohanan; Alwarappan, Subbiah
Highlights: Extensive discussion on various synthetic methods of graphene quantum dots (GQDs). Post synthetic methods for purification and surface functionalization of GQDs. Properties of GQDs with special emphasis on optical properties. Sensor designs based on GQDs. Transition metal dichalcogenides QDs based sensors. Abstract: Graphene quantum dot (GQDs) is a zero dimensional member in the carbon family and is usually considered as a chopped fragment from a graphene sheet. The unique features exhibited by GQDs are due to the combined structural properties of graphene endowed with the edge effects and quantum confinement properties. As a result, GQDs find widespread applications in biosensing, bioimaging, drug delivery, solar cells, photo detectors, batteries, light emitting diodes, supercapacitors etc. In this review, our first key focus is on various top-down and bottom-up approach employed for the synthesis of engineered GQDs. Following this, a brief discussion on the post treatment methods available for the purification of the GQDs is also presented. Sensors based on quantum dots systems of transition metal dichalcogenides (TMDs) are also briefly discussed. The key focus in this review is on the usefulness of the engineered/hetero atom-doped GQDs and TMDQDs in optical and electrochemical sensor design and their applications during chemical and bioanalysis. Finally, we have also briefly mentioned about the existing bottlenecks in the sensors fabrication and a perspective to overcome the odds.